Mathematical modelling and design of counterweights for unbalanced links / Abdullah Jamil ... [et al.] - Jamil, Abdullah; Baharom, M. B.; Lemma, T. A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper proposes a procedure to mathematically model the counterweight of rotating links based on calculations according to design requirements. The main objective of the research is to introduce an effective method to design the counterweight using CAD drawing. A parameterized equation is formulated with the help of counterweight geometry derived from a typical crankshaft counterweight design. Using the law of moments and Center of gravity of links, the geometry of counterweight can be found using the formula that is parameterized with a single variable. The results were obtained by finding the roots of the final equation. The method was found to be effective in term of time consumption rather than implementing the iterative method